Trigeminal neuralgia in a young woman preceding multiple sclerosis. - Juliatti, Felipe Cenicio; Braga, Luiza Mansur; Júnior, José Lopes de Vasconcelos; Arthuzo, Lorrane Campidelli (Headache Medicine, 2024)
Introduction: Trigeminal neuralgia (TN) may be a manifestation of a demyelinating disease with a 20-fold higher prevalence of TN in this group of patients. Objective: Demonstrate the presence of trigeminal neuralgia as an initial manifestation of multiple sclerosis. Conclusion: Patients with Multiple Sclerosis may present trigeminal neuralgia as first symptom of MS. TN is one of the main causes of neuropathic pain.